Exploring Intercultural Understandings of Mental Health for School Contexts - Holt, Regan Carley (Journal of the Canadian Association for Curriculum Studies, 2020)
What does mental health mean? As an educator, I have noticed that mental health is a concept viewed by many students and colleagues as “loaded” with stigma and often referenced as a shameful form of illness. It is estimated that one in five high school students will suffer from a mental illness, with the majority not accessing mental health services due to the stigma associated with the illness (Bowers et al., 2013). Wondering how particular understandings of mental health might influence pedagogical approaches, I conducted a preliminary literature review across caregiver professions, including nursing, social work, psychology, medicine and education. Findings indicated that medicalized mental health definitions framed by Western philosophy were prevalent. Conceptions of mental health that represent different cultural perspectives, pluralistic understandings (diverse epistemologies), or other ways of being (ontologies) are isolated and excluded. This roundtable session will be guided by a hermeneutic approach that aims to broaden understandings by asking participants to consider the concept of mental health within cultural traditions, histories, stories, languages, experiences, subjectivities and relations. To further discussion, contemporary conceptualizations are presented through literature, images and symbols.